Gene Expression Changes in Progression of Cervical Neoplasia Revealed by Microarray Analysis of Cervical Neoplastic Keratinocytes. Issue 4 (April 2015) - Rotondo, John Charles; Bosi, Silvia; Bassi, Cristian; Ferracin, Manuela; Lanza, Giovanni; Gafà, Roberta; Magri, Eros; Selvatici, Rita; Torresani, Stefania; Marci, Roberto; Garutti, Paola; Negrini, Massimo; et al.
Abstract To evaluate the gene expression changes involved in neoplastic progression of cervical intraepithelial neoplasia. Using microarray analysis, large‐scale gene expression profile was carried out on HPV16‐CIN2, HPV16‐CIN3, and normal cervical keratinocytes derived from two HPV16‐CIN2, two HPV‐CIN3 lesions, and two corresponding normal cervical tissues, respectively. Differentially expressed genes were analyzed in normal cervical keratinocytes compared with HPV16‐CIN2 keratinocytes and in HPV16‐CIN2 keratinocytes compared with HPV16‐CIN3 keratinocytes; 37 candidate genes with continuously increasing or decreasing expression during CIN progression were identified. One of these genes, phosphoglycerate dehydrogenase, was chosen for further characterization. Quantitative reverse transcription‐polymerase chain reaction and immunohistochemical analysis confirmed that expression of phosphoglycerate dehydrogenase consistently increases during progression of CIN toward cancer. Gene expression changes occurring during CIN progression were investigated using microarray analysis, for the first time, in CIN2 and CIN3 keratinocytes naturally infected with HPV16. Phosphoglycerate dehydrogenase is likely to be associated with tumorigenesis and may be a potential prognostic marker for CIN progression. J. Cell. Physiol. 230: 806–812, 2015. © 2014 Wiley Periodicals, Inc.